An ordinal minimax theorem - Brandt, F; Brill, M; Suksompong, W (Elsevier, 2016)
In the early 1950s Lloyd Shapley proposed an ordinal and set-valued solution concept for zero-sum games called weak saddle. We show that all weak saddles of a given zero-sum game are interchangeable and equivalent. As a consequence, every such game possesses a unique set-based value.